Corporate Size, Performance and Governance can affect the Audit Delay? - Sugeng Suroso (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this research is to find the effect of firm size, financial performance, and good corporate governance on audit delay. The research was carried out using consumer goods industrial sector companies listed on the IDX from 2017 to 2019. The data used is secondary data and is obtained in the report of each company. The research method is carried out with a quantitative approach which is analyzed using multiple regression analysis. There are 52 companies in the consumer goods industry sector that are used as samples for a period of 3 years. The results of this study prove that; Firm size has a negative and insignificant effect; financial performance has a significant positive effect; and Good Corporate Governance have a negative and significant effect.